LEGAL CERTAINTY OF FINANCING OF MERAH PUTIH VILLAGE COOPERATIVES: INSTITUTIONAL ANALYSIS BETWEEN THE PRINCIPLE OF COOPERATIVE INDEPENDENCE AND STATE INTERVENTION - Hasanudin, Adnan; Winanti , Atik; Jilena Meliala, Aurora (PT. Jurnal Center Indonesia Publisher, 2025)
This study examines the legal certainty of financing for Indonesia's Desa Merah Putih Cooperative (KDMP) initiative, analyzing the institutional tension between cooperative independence and state intervention. Rooted in the constitutional mandate for cooperatives as a cornerstone of the Indonesian economy, the KDMP program aims to establish 80,000 village-level cooperatives through state-facilitated credit lines and technical assistance. However, this top-down model raises concerns about undermining cooperative autonomy enshrined in Law No. 25/1992 and the principle of subsidiarity. Employing a normative juridical research design, this study draws on secondary data from legal literature and primary legal materials to systematically examine relevant norms and doctrines. Findings reveal a tenuous alignment between state financing mechanisms and cooperative autonomy, primarily due to the proposed reliance on state-owned bank credit lines rather than direct state budget grants, leading to legal ambiguity regarding accountability and oversight. The potential for mass loan defaults and the contentious use of Village Funds as collateral further complicate legal certainty and risk hidden liabilities. Comparative insights from India's Amul cooperative and the Philippines' barangay cooperatives illustrate successful models where government acts as a facilitator without impinging on cooperative self-governance or member control. This study advocates for a recalibrated regulatory approach featuring transparent oversight, proportional supervision, and participatory decision-making to reconcile developmental imperatives with cooperative principles, ultimately enhancing legal certainty and ensuring that state-supported cooperatives remain genuinely member-driven enterprises.